How is the accounting academy playing the publication game? Type of authorship and international diversity and networks - Lourenço, I. C.; Branco, M. C.; Azevedo, R.; Oliveira, J. (XVIII Encuentro Internacional AECA, 2018)
This study analyses 3,262 papers published in 18 accounting top journals between 2013 and 2017. We have classified these papers based on the type of authorship in Solo (only one author), Homogeneous Multiple (more than one author from the same university), Heterogeneous National (with authors from different universities from the same country) and Heterogeneous International (with authors from universities belonging to different countries). We perform a set of cluster analysis, which suggests a classification of the papers distinguishing between two broad groups of journals: the North American journals, where there is a predominance of national networks and where most authors are affiliated to a North American journal, and the Non-North American journals, where there is a predominance of international networks and a higher level of authors’ international diversity. Regarding the heterogeneous international authorship, we perform a social network analysis suggesting that researchers affiliated with North-American universities and their counterparts from European universities seem to ignore each other. Whereas the first have been publishing mainly with co-authors affiliated with universities from Asia, the latter have been publishing articles with one another.